The Search and Seizure Exclusionary Rule (1989)
The fourth amendment guarantees the right of the people to be secure in their persons, houses, papers, and effects, against unreasonable searches and seizures. This guaranty is not self-executing, however, and the courts and criminal justice systems in this country have long been bedeviled by questions concerning appropriate methods of ensuring its observance. As a result of the Supreme Court's decisions in Weeks v. United States and Mapp v. Ohio, the method principally relied upon today is a judicially created rule excluding from criminal trials evidence obtained in violation of the defendant's fourth amendment rights. The search and seizure exclusionary rule is subject to a number of well-founded criticisms. First, the rule has no support in the original intent or meaning of the Framers of the Constitution. Second, the validity of the rule's deterrence rationale has yet to be demonstrated. Third, among its other drawbacks, the rule impairs significantly the search for truth in criminal justice. Finally, alternative methods for deterring and redressing fourth amendment violations exist or could be created, and those alternatives would be more effective and less costly than the exclusionary rule